Unconditional and Conditional Takeover Offers: Experimental Evidence - Kale, Jayant R.; Noe, Thomas H. (Review of Financial Studies, 1997)
This article compares the predictions of finite-shareholder models of conditional and unconditional takeover offers with the outcomes of laboratory experiments. In addition to differentiating between types of offers, the experimental designs span small and large firms as well as different levels of offer premiums. It is found that in unconditional offers to large groups of subjects (28–40), the symmetric Nash equilibrium predicts observed tendering frequencies quite accurately. For other experimental designs, the results are mixed. The analysis of shareholder tendering strategies from the experiment yields insights into (I) the effects of takeover offer designs, (ii) the appropriateness of finite-shareholder models for research, and (iii) the costs of free riding when shareholders are nonatomistic.